Traumatic bifrontal extradural haematoma resulting from superior sagittal sinus injury: case report. (11th May 2015) - Bimpis, Alexios; Marcus, Hani J; Wilson, Mark H
Lesson: Traumatic bilateral extradural haematoma resulting from injury to the superior sagittal sinus is rare; in such cases, early surgical evacuation of the haematoma and control of bleeding from the sinus can achieve an excellent patient outcome.